JUMLAH TROMBOSIT PASIEN DHF DENGAN TERAPI KONSENTRAT TROMBOSIT - Astuti, Dewi; setianingrum, Atika; Navita, Delly; Maharani, Eva Ayu (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Bacground: Dengue fever is a disease caused by the dengue fever virus. Clinical manifestations of dengue fever can cause bleeding associated with thrombocytopenia. Platelet transfusions are used to manage dengue fever. Previous research found that platelets count after Apheresis Platelet transfusion was higher than using Platelet Concentrate. This research will be carried out to determine the number of platelets in dengue fever patients with platelet concentrate therapy. Methdes : The research design used was a descriptive observational study using 40 data on platelet count examinations before and after platelet concentrate transfusion at the hospital. Dr. Iqbali Taufan in 2021-2022. Results: The frequency of DHF patients with platelet concentrate therapy was 70% male and 30% female. DHF patients with platelet concentrate therapy are predominantly adults (26-45 years) was 70%. The results of the platelet count before the transfusion of Thrombocy Concentrate from a total of 40 patients were minimum 8,000/µL, maximum 87,000/µL, and an average count was 23,875/µL. The platelet count after transfusion of Platelet Concentrate were minimum 16,000/µL, maximum of 185,000/µL, and an average count was 92,350/µL. Conclusion: The frequency of DHF patients with platelet concentrate therapy is 70% male and 70% adult (26-45 years). The average number of platelets before the Platelet Concentrate was transfused was 23,875/µL and after the transfusion was 92,350/µL. Keyword: Platelet concentrate, Pre transfusion, Post transfusion